1980
DOI: 10.1007/bf01869003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of transient electrical properties to active sodium transport by toad urinary bladder

Abstract: Application of voltage pulses of 10 mV for periods of 9 sec across toad urinary bladder elicits a rapid deflection in transepithelial current. Frequently, the current decays back towards its baseline value during the course of the polarizing pulse. This transient phenomenon can be induced, or its magnitude increased, by raising the mucosal or serosal Na+ concentration. The transient can be abolished by sufficiently hyperpolarizing the tissue (rendering serosa positive to mucosa), by inhibiting transcellular Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

1981
1981
1996
1996

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
3
14
1
Order By: Relevance
“…Furthermore, the asymmetrical transient responses of transepithelial current-to-voltage pulses sometimes observed (Fig. 1) has suggested that some of the time-dependent changes may reflect polarization effects noted with longer pulses (Weinstein et al, 1980), and not solely reflect capacitative transients. In studying the effects of CI-on Na + transport, we have therefore chosen to use voltage pulses of 16-to 32-msec duration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the asymmetrical transient responses of transepithelial current-to-voltage pulses sometimes observed (Fig. 1) has suggested that some of the time-dependent changes may reflect polarization effects noted with longer pulses (Weinstein et al, 1980), and not solely reflect capacitative transients. In studying the effects of CI-on Na + transport, we have therefore chosen to use voltage pulses of 16-to 32-msec duration.…”
Section: Discussionmentioning
confidence: 98%
“…Step changes in transepithelial voltage or current can result in time-dependent changes in the conju- gate parameter, which are not ascribable to simple capacitative responses (Weinstein et al, 1980). At least some of these time-dependent effects likely reflect polarization potentials and impedances resulting from ionic translocations during prolonged stimulation.…”
Section: Measurements Of P~amentioning
confidence: 98%
“…This concept is supported by the reports that: (i) Sufficient intracellular sodium is accumulated during potassium depletion of toad bladder epithelium to support such exchange . (ii) Negative feedback between intracellular sodium activity a~ and apical sodium permeability (P~) could provide the basis for the reduced apical sodium entry following potassium depletion (Erlij & Smith, 1973;Lewis, Eaton & Diamond, 1976;Cuthbert & Shum, 1977;Turnheim, Frizzell & Schultz, 1978;Weinstein et al, 1980;Chase & A1-Awqati, 1979); this feedback may be mediated by changes in intracellular calcium activity (Blaustein, 1974;Grinstein & Erlij, 1978;Taylor & Windhager, 1979;Lee, Taylor & Windhager, 1980;Chase & A1-Awqati, 1981), and (iii) Computer simulation has permitted qualitative replication of the time-lag phenomenon, once the feedback between a~a and P~P, is introduced into the model (Civan & Bookman, 1982). Since these pieces of evidence are indirect, a more direct testing of the thesis was attempted in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Since transients occur in the absence of Cl-in the bathing media (isethionate as substitute, Weinstein et al 1980; gluconate as substitute, personal observation), process B appears not to involve Cl-currents. Thus changes in the basolateral K+ conductance appear to offer the best explanation for the transient phenomenon.…”
Section: Discussionmentioning
confidence: 99%